Empathy and Its Relationship With Social Functioning in Individuals at Ultra-High Risk for Psychosis - Kuis, Daan Jan; van de Giessen, Tara; de Jong, Steven; Sportel, Bouwina Esther; Boonstra, Nynke; van Donkersgoed, Rozanne; Lysaker, Paul H.; Hasson-Ohayon, Ilanit; Pijnenborg, Gerdina Hendrika Maria (Frontiers in Psychiatry, 2021)
Introduction: Social functioning is often impaired in the ultra-high-risk (UHR) phase of psychosis. There is some evidence that empathy is also impaired in this phase and that these impairments may underlie difficulties in social functioning. The main aim of this study was to investigate whether cognitive and affective empathy are lower in people in the UHR phase of psychosis in comparison to healthy controls, and whether possible impairments have the same magnitude as in people with schizophrenia. A second aim was to examine whether there is a relationship between empathy and social functioning in individuals in the UHR phase. Method: Forty-three individuals at UHR for psychosis, 92 people with a schizophrenia spectrum disorder, and 49 persons without a psychiatric disorder completed the Interpersonal Reactivity Index (IRI), Questionnaire of Cognitive and Affective Empathy (QCAE), and Faux Pas as instruments to measure empathy. The Time Use survey was used to measure social functioning. MAN(C)OVA was used to analyse differences between groups on empathy and social functioning, and correlations were calculated between empathy measures and social functioning for each group. Results: The UHR group presented significantly lower levels of self-reported cognitive empathy than the healthy controls, but not compared to patients with SSD, while performance-based cognitive empathy was unimpaired in the UHR group. On the affective measures, we found that people with UHR and patients with SSD had significantly higher levels of self-reported distress in interpersonal settings compared to healthy controls. In the UHR group, perspective-taking was negatively associated with time spent on structured social activities. In the SSD group, we found that structured social activities were positively associated with perspective-taking and negatively associated with personal distress in interactions with others. Lastly, in people without mental illness, social activities were positively associated with performance-based perspective-taking. Conclusion: Impairments in subjective cognitive empathy appear to be present in the UHR phase, suggesting that difficulties in interpreting the thoughts and feelings of others precede the onset of psychotic disorders. This can inform future interventions in the UHR phase.